Accelerated corrosion of pipeline steel and reduced cathodic protection effectiveness under direct current interference. (1st September 2017) - Qian, Shan; Cheng, Y. Frank
Highlights: Measured the potential of pipeline steel under direct current (DC) densities. Quantified the accelerated corrosion rate of the steel under DC interference. Determined the shift of cathodic protection potential in the presence of DC. Determined the electrolyte alkalinisation caused by DC stray current. Abstract: In this work, corrosion of an X52 pipeline steel at various direct current (DC) densities was investigated in an extracted soil solution by potential and pH measurements, weight-loss testing and optical microscopy. It was found that the DC stray current could polarize, either anodically or cathodically, the steel at the anodic and cathodic zones, respectively, resulting in accelerated corrosion of the steel and the cathodic reduction of dissolved oxygen. The CP potential was not maintained at the applied value under the DC interference, and was shifted to positive and negative directions in the anodic and cathodic zones, respectively. The pipeline suffered from both anodic and cathodic DC interferences. The steel in the anodic zone cannot be protected, at least not fully protected, by the CP from corrosion. The solution alkalization in the cathodic zone would be further enhanced due to the combined effect of DC and CP on cathodic reaction. The implications of the DC interference on pipeline integrity were discussed.